Accounting Analysis in Accounts Receivable Management to Minimize the Risk of Uncollectible Receivables at ALS Hotel and Resort - N L M Puri Suwantari; I M Ariana; P Adi Suprapto (Journal of Applied Sciences in Accounting, Finance, and Tax, 2020)
ALS Hotel and Resort applies a credit policy in its operations. The high level of credit sales owned by the hotel, which is followed by the high number of delinquent receivables, has the potential to become uncollectible accounts. Therefore, proper management of accounts receivable is required. This research aims to determine the effect of the application of accounts receivable accounting treatment on the effectiveness of accounts receivable management in minimizing the risk of uncollectible receivables at ALS Hotels and Resort. This research used data obtained through unstructured interviews, observation, and documentation. The data analysis technique used was descriptive qualitative analysis technique and quantitative descriptive. The results of this research showed that the accounting treatment for ALS Hotel and Resort accounts receivable was following the Financial Accounting Standards. Accounts receivable management effectiveness was not yet effective because hotel management has not considered all 5C principles. The receivables collection policy has not been optimal due to the receivable turnover ratio and average collection period that show sub-standard results and impact on the arrears and billing ratios. The suitability of accounting treatment for accounts receivable provides relevant information that the management of accounts receivable to minimize uncollectible receivables has not been effective.